Design variations in Moroccan calligraphy composition (Al-Academy, 2024)
This research was concerned with studying the design diversities in Moroccan calligraphy formations, as Arabic calligraphy received great attention from calligraphers, and was distinguished by the multiplicity of its types, shapes, and names, which indicates the development that Arabic calligraphy has witnessed. Through the context of these developments, Moroccan calligraphy came to express the role of Moroccans and their contribution to its development. The research included four chapters. The first chapter included the research problem, which was represented by the following question: What are the design diversities in the compositions of Moroccan calligraphy? The researcher set the goal of the research, which is: revealing the design diversities in the compositions of Moroccan calligraphy, while the second chapter included two sections: the first: design diversity in the Moroccan calligraphy, and the second: the structure of the composition in the Moroccan calligraphy. The third chapter included the research procedures, and relied on the descriptive approach (method of analysis Content) The research community reached (51) samples of Moroccan script, and the research sample was intentionally selected with (5) models. This is followed by analysing the samples according to the research tool represented by the analysis form, the validity of which was confirmed by a group of specialists in this field, and then followed by Chapter Four. Which included results, conclusions, recommendations and proposals